POLICY ON ANESTHESIA SERVICES FOR HYPERTENSION PATIENTS IN PRE, INTRA, AND POST ANESTHESIA BY SPECIALIST ANESTHETISTS AND ANESTHESIA CAREGIVERS - Ambarika , Rahmania; Rekso Negoro, Widigdo (HEARTY, 2025)
Anesthesia services are an important component of medical services in surgical procedures and other invasive procedures that aim to reduce or eliminate pain during the procedure. The success of anesthesia is not only triggered by the anesthetic technique used, but the patient's clinical condition also has an influence. Specialist anesthetists and anesthetists play an important role in determining patient suitability, adjusting the appropriate anesthesia technique, and monitoring during and after the procedure. Hypertension is a chronic disease that requires special attention in anesthesia services because of a higher risk of blood pressure fluctuations, organ perfusion disorders, and cardiovascular events such as stroke and myocardial infarction. This research aims to examine the anesthesia service policy at Pindad Turen Hospital and analyze the obstacles experienced by medical personnel in its implementation. The results of this study show that there is a main problem in implementing anesthesia service policies for hypertensive patients in hospitals, namely that there is no standardization of policies or SOPs related to determining the suitability of hypertensive patients to undergo anesthesia and there are differences in perception between specialist anesthetists and anesthetists, especially regarding safe blood pressure limits and recording the results of pre-anesthesia evaluations. From the problems found, a situation analysis was carried out using fishbone, USG, and SWOT diagrams, and priority problems were found, namely the absence of appropriate blood pressure standards for hypertensive patients and the absence of a special SOP for anesthesia services for hypertensive patients. These problems have the potential to affect patient safety during anesthesia. The intervention was carried out through outreach and training to health workers and it was proven to increase knowledge and uniformity of perception of medical staff in determining the suitability of hypertensive patients as evidenced by an increase in evaluation results from 2.8 (pretest) to 5 (posttest).